Synthesis, Spectroscopy, Semi‐empirical and Biological Activities of Organotin(IV) Complexes with o‐Isopropyl Carbonodithioic Acid. Issue 8 (14th August 2015) - Javed, Fatima; Ali, Saqib; Shahzadi, Saira; Khalid, Nasir; Tabassum, Saira; Khan, Imran; Sharma, Saroj K.; Qanungo, Kushal
Abstract New organotin(IV) complexes have been synthesized by treating potassium o‐isopropyl carbonodithioate with R2SnCl2/R3SnCl in 1 : 2/1 : 1 M/L ratio. All complexes have been characterized by IR and NMR (1H, 13C) spectroscopy. IR results shows that ligand acts as bidentate which is also confirmed by semi‐empirical study. NMR data reveals four coordinated geometry in solution. Computed positive heat of formation shows that complex 5 is thermodynamically unstable. UV/visible spectroscopy was used to assess the mode of interaction and binding of the complexes with DNA which shows that complex 5 exhibits higher binding constant as compared to complex 3. In protein kinase inhibition assay, compound 3 was found most active, while other biological activities shows that triorganotin(IV) complexes are biologically more active as compared to diorganotin(IV) complexes.